The Influence of ESG and Investment on Equity Ratio on Firm Value in the ASEAN Mining Sector - Hastalona, Dina; Sadalia, Isfenti (Institut Bisnis dan Informatika Kesatuan, 2025)
This study is to investigate the impact of the Investment to Equity Ratio and the Environmental, Social, and Governance (ESG) Score on firm value, as measured by Tobin’s Q, in mining businesses throughout ASEAN between 2019 and 2024. The Common Effect Model (CEM), which is based on 96 observations from 16 companies over a six-year period, is used in the research’s panel data regression approach. The findings indicate that Tobin’s Q is positively and significantly impacted by ESG Score, with a coefficient of 0.0066 (p = 0.0042). The Investment to Equity Ratio, on the other hand, shows a statistically negligible negative effect (p = 0.2241). The model can account for 8.8% of the variation in company value, according to the R-squared value of 0.088. These results demonstrate how ESG practices can improve firm valuation and market reputation, but they also point to the need for more research on the function of investment finance arrangements. When developing sustainability plans and capital structure optimization techniques for the ASEAN mining industry, managers and investors can benefit from the practical implications of this study.